2013
DOI: 10.1155/2013/628759
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Efficiently Interfaced Steel Concrete Composite Deck Slabs

Abstract: The strength of the composite deck slab depends mainly on the longitudinal shear transfer mechanism at the interface between steel and concrete. The bond strength developed by the cement paste is weak and causes premature failure of composite deck slab. This deficiency is effectively overcame by a shear transferring mechanism in the form of mechanical interlock through indentations, embossments, or fastening studs. Development of embossment patterns requires an advanced technology which makes the deck profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 9 publications
0
7
0
6
Order By: Relevance
“…It is concluded that using embossed profile increases the load carrying capacity and delays the delamination. In order to improve the shear strength, Lakshmikandhan et al [14] investigated three different shear transferring mechanisms namely mechanical interlock through indentations, embossments, and fastening studs. The mechanical shear connectors increase the load and bending moment capacity and also increase stiffness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is concluded that using embossed profile increases the load carrying capacity and delays the delamination. In order to improve the shear strength, Lakshmikandhan et al [14] investigated three different shear transferring mechanisms namely mechanical interlock through indentations, embossments, and fastening studs. The mechanical shear connectors increase the load and bending moment capacity and also increase stiffness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence partial stiffness should be considered while calculating deflection. K. N. Lakshmikandhan et al, 2013 [7], have experimentally studied three types of mechanical connector and found that three connector schemes exhibited full shear interaction and produced a negligible slip.…”
Section: Me A-h Eldib 2009mentioning
confidence: 99%
“…Experiment is designed with a total of 5 specimens which were divided into 3 groups, to simulate a simply supported singlespan bridge deck [8][9][10][11][12][13][14]. Design parameters of the specimens are shown in Table 1.…”
Section: Experimental Situationmentioning
confidence: 99%